"Розумне" підприємство – основні властивості та напрямки розвитку - Мейтус, В.Ю.; Морозова, Г.П.; Таран, Л.Ю.; Козлова, В.П.; Музальова, В.О. (Control systems & computers, 2020)
Розглянуто парадигму розумного підприємства, сформульованоі основні вимоги, що забезпечують виконання цієї парадигми, запропоновано схему інтелектуалізації аналізу зовнішнього оточення розумного підприємства з використанням нового механізму подання знань про це оточення. Розробляються методи, спрямовані на підвищення інтелектуального рівня існуючого виробництва. Цей підхід дає змогу підвищити загальний рівень інтелекту, пов'язаного з виконанням головних функцій підприємства. The purpose of the work is to consider the relationship between the digital economy and the smart enterprise, the paradigm and the basic properties of the smart enterprise, the creation of intelligent algorithms as the basis for the analysis and solution of problems that arise during the operation of the smart enterprise. The research method is based on well-known forms of representing the structure of a smart enterprise, together with the use of a new form of knowledge representation designed to build intelligent systems. Result. The paradigm of a smart enterprise is considered, the basic requirements that ensure the fulfillment of this paradigm are formulated, the scheme of intellectualization of the analysis of the external environment of a smart enterprise using the mechanism for representing knowledge about this environment is considered. Цель работы – рассмотреть отношения между цифровой экономикой и «умным» предприятием, парадигму и основные свойства «умного» предприятия, создание интеллектуальных алгоритмов, как основы анализа и решения проблем, возникающих в процессе работы «умного» предприятия. Метод исследования основан на известных формах представления структуры «умного» предприятия вместе с использованием новой формы представления знаний, разработанной для построения интеллектуальных систем. Результат. Рассмотрена парадигма «умного» предприятия, сформулированы основные требования, обеспечивающие выполнение этой парадигмы, рассмотрена схема интеллектуализации анализа внешнего окружения «умного» предприятия с использованием механизма представления знаний об этом окружении.